2021
DOI: 10.1093/eurheartj/suab093
|View full text |Cite
|
Sign up to set email alerts
|

New prevention scenarios: polygenic risk

Abstract: Although coronary heart disease is a highly preventable disease, it is still the leading cause of morbidity and mortality in developed countries. This is also due to the fact that the risk models used in clinical practice have proved ineffective in identifying people at risk: up to 30% of cases of myocardial infarction do not have traditional risk factors used in risk estimation models. Although the genetic component of myocardial infarction has been known for many years, with an inheritance rate of between 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Cardiovascular diseases are part of complex or multifactorial diseases, in which numerous causes converge, not all of which are easily recognizable 1 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiovascular diseases are part of complex or multifactorial diseases, in which numerous causes converge, not all of which are easily recognizable 1 …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the research on cardiovascular prevention and risk stratification focuses, in addition to large genomic datasets, on biomarkers, 3 metabolic phenotypes, imaging, 4,5 both ultrasound and radiological, and on their integration, favoured by artificial intelligence applications 1,6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is calculated according to the weighted accumulation of thousands of risk mutations carried by individuals, and aims to quantify the cumulative effects of a large number of SNPs or genes (Dudbridge, 2013). With the deepening of GWAS research and application transformation research, the application of the PRS model in risk assessment of common diseases has been verified (Dai et al, 2019;Boccanelli and Botta, 2021;Lu et al, 2021). However, at present, the clinical research of PRS in self-reported childhood maltreatment is still lacking.…”
Section: Introductionmentioning
confidence: 99%